A comparison of ultrasonic measurement techniques for the maternal cervix in the second trimester. Issue 3 (August 2015) - O'Hara, Sandra; Zelesco, Marilyn; Sun, Zhonghua
Abstract: Introduction: The appropriate ultrasound technique to assess the maternal cervical length in women at low risk of preterm birth is yet to be established. This study aimed to determine the accuracy of different ultrasound approaches for measuring the maternal cervix in patients between 17 and 22 weeks gestation. Methods: The prospective study recruited 50 patients who were at a low risk of preterm birth. All measurements were acquired by one operator who was blind to the measurements being acquired in all approaches. The cervical length was registered using the transabdominal approach with a full and empty bladder, the transperineal approach and the transvaginal. The transvaginal approach was used as the reference measurement. Results: The transabdominal full bladder, post void, transperineal and transvaginal measurements were obtainable in 50, 49, 45 and 50 participants respectively. The transabdominal post void measurements showed a bias of −0.06 mm from perfect agreement with transvaginal. The transperineal measurements showed a bias of −0.16 mm. The transabdominal full bladder measurements were positively biased by 14.05 mm (p < 0.05). All transabdominal post void cervical lengths of 30 mm or greater registered a transvaginal cervical length greater than 25 mm in this study. Conclusion: The cervix should not be assessed in the transabdominal approach with a full maternal bladder due to overestimation of cervical length. Transvaginal cervical length can be reproduced accurately by post void transabdominal cervical length in most cases. Transperineal cervical length should be considered if transvaginal cervical length is contraindicated.